2018
DOI: 10.1186/s40104-018-0303-8
|View full text |Cite
|
Sign up to set email alerts
|

Amylopectin structure and crystallinity explains variation in digestion kinetics of starches across botanic sources in an in vitro pig model

Abstract: BackgroundStarch is the main source of energy in commonly used pig diets. Besides effects related to the extent of starch digestion, also several effects related to variation in digestion rate have recently been demonstrated in non-ruminants. Different rates of starch digestion in animals and in in vitro models have been reported, depending on the botanic origin of starch. Starches from different botanic sources differ widely in structural and molecular properties. Predicting the effect of starch properties on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 43 publications
4
79
0
3
Order By: Relevance
“…Similarly, legume seeds are known to be high in naturally occurring RS, partly because their starches are trapped inside the cotyledon cell parenchyma ( Würsch, 1986 ; Berg et al, 2012 ). Tuber starches like potato may also have some resistance to enzymatic digestion because its granules are large and smooth ( Dhital et al, 2017 ; Martens et al, 2018 ). However, all these reports have been conducted with starch ingredients alone, but pet foods are composed of other ingredients which are ground, mixed, and then cooked or processed in some manner.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, legume seeds are known to be high in naturally occurring RS, partly because their starches are trapped inside the cotyledon cell parenchyma ( Würsch, 1986 ; Berg et al, 2012 ). Tuber starches like potato may also have some resistance to enzymatic digestion because its granules are large and smooth ( Dhital et al, 2017 ; Martens et al, 2018 ). However, all these reports have been conducted with starch ingredients alone, but pet foods are composed of other ingredients which are ground, mixed, and then cooked or processed in some manner.…”
Section: Introductionmentioning
confidence: 99%
“…The digestive enzyme α-amylase is responsible for the breakdown of the starch into dextrins (maltotriose, DP3) and maltose (DP2), which are in turn digested by epithelial maltase, resulting in glucose monomers. It is often suggested that the amylose content is the most important factor in determining the rate of digestion and absorption as well as the related glycemic response, but recent research shows that the picture is more complex (25). It appears that the interaction between the molecular and granular structure (helix formation, number of pores, size of the molecule, amylopectin sidechain length distribution and crystalline structure, the latter two being the most important) causes the variation in the rate of digestion across botanical sources (25).…”
Section: Same Degree Of Polymerization But Different Effectsmentioning
confidence: 99%
“…The potential of starch to affect the blood glucose response, expressed as a glycemic index (GI) value, can therefore vary considerably depending on the content of amylopectin and amylose ( 26 28 ). Interestingly, despite only small differences in amylose content, in vitro cumulative starch hydrolysis shows that wheat starch is more rapidly digested than potato starch (being the most resistant starch), with corn, high-amylose corn, and pea starch having intermediate values ( 25 ).…”
Section: Chemical Classification Of Saccharides and Its Meaningmentioning
confidence: 99%
“…In vitro studies showed that these intrinsic properties of starch cause variation in starch digestion kinetics. Although many of the structural and molecular properties of starch are inter-related within a botanic source of starch, B-type crystalline structure and long amylopectin side chains generally reduce digestion rate across botanic sources (1,10,11) . Within starch of cereal origin, the number of pores Abbreviations: BW, body weight; DC, digestion coefficient; DP, degree of polymerisation; EB, barley starch in extruded form; GA, high-amylose maize starch in ground form; GB, barley starch in ground form; GIT, gastrointestinal tract; GM, maize starch in ground form; HA, high-amylose; IA, high-amylose maize starch in isolated form; IB, barley starch in isolated form; IM, maize starch in isolated form; MRT, mean retention time; RDS, rapidly digestible starch; RS, resistant starch; SDS, slowly digestible starch; SEM, scanning electron microscope; SI, small intestine.…”
mentioning
confidence: 99%
“…Within starch of cereal origin, the number of pores Abbreviations: BW, body weight; DC, digestion coefficient; DP, degree of polymerisation; EB, barley starch in extruded form; GA, high-amylose maize starch in ground form; GB, barley starch in ground form; GIT, gastrointestinal tract; GM, maize starch in ground form; HA, high-amylose; IA, high-amylose maize starch in isolated form; IB, barley starch in isolated form; IM, maize starch in isolated form; MRT, mean retention time; RDS, rapidly digestible starch; RS, resistant starch; SDS, slowly digestible starch; SEM, scanning electron microscope; SI, small intestine. and the amylopectin:amylose ratio are positively correlated with in vitro digestion rate (9,11) . Several in vivo studies confirm these in vitro findings, as starch with a high-amylose (HA) content and B-type crystalline structure positively correlate with lower incremental plasma glucose concentrations in pigs (1,12) .…”
mentioning
confidence: 99%